The music producer's survival guide chaos, creativity, and career in independent and electronic music - Jackson, Brian M. (Sound on sound presents, 2018)
A music-career book like no other, The Music Producer's Survival Guide offers a wide-ranging, exploratory, yet refreshing down-to-earth take on living the life of the independent electronic music producer. If you are an intellectually curious musician/producer eager to make your mark in today's technologically advanced music business, you're in for a treat. This new edition includes industry and technological updates, additional interviews, and tips about personal finances, income, and budgets. In this friendly, philosophical take on the art and science of music production, veteran producer, engineer, and teacher Brian Jackson shares clear, practical advice about shaping your own career in today's computer-centric "home-studio" music world. You'll cover music technology, philosophy of music production, career planning, networking, craft and creativity, the DIY ethos, lifestyle considerations, and much more. Brian's thoughtful approach will teach you to integrate your creative passion, your lifestyle, and your technical know-how. The Music Producer's Survival Guide is the first music-production book to consider the influence of complexity studies and chaos theory on music-making and career development. It focuses on practicality while traversing a wide spectrum of topics, including essential creative process techniques, the TR-808, the proliferation of presets, the butterfly effect, granular synthesis, harmonic ratios, altered states, fractal patterns, the dynamics of genre evolution, and much more. Carving out your niche in music today is an invigorating challenge that will test all your skills and capacities. Learn to survive--and thrive--as a creative-technical professional in today's music business, with the help of Brian Jackson and The Music Producer's Survival Guide!